Tubercular disease caused by bacillus of Calmette-Guerin administered as a local adjuvant treatment of relapsing bladder carcinoma. Pathogenetic, diagnostic and therapeutic issues, and literature review - Manfredi, Roberto; Dentale, Nicola; Piergentili, Benedetta; Pultrone, Cristian; Brunocilla, Eugenio (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2012)
Two exemplary case reports of respiratory granulomatous infection caused by bacillus of Calmette-Guérin (BCG) in patients who were repeatedly treated with local, intravesical adjuvant BCG therapy for a relapsing transitional bladder carcinoma, are outlined and discussed, on the ground of the cumbersome diagnostic and differential diagnostic process (especially when a prior tuberculosis and a concurrent chronic obstructive pulmonary disease are of concern), and an updated literature revision. Only four cases of respiratory BCG-itis (pulmonary tuberculosis-like forms), have been reporteduntil now to the best of our knowledge (two of them following bladder instillation of BCG). One episode of ours represents the first described case with a dual, concomitant granulomatous localization of BCG-itis, also involving the genitourinary tract.